Measurement of CaO-SiO2-CaCl2 slag density by an improved Archimedean method - WANG, YE; Morita, Kazuki (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
In order to optimize the removal of boron during the refining of slag to obtain solar grade silicon, the density of molten slag was measured by an improved Archimedean method within a temperature range of between 1073 and 1373 K. This found that the density of molten slag at 1723 K can be deduced from a linear fitting, and that the slag density decreases with increasing temperature. However, there is a reduction in slag density with decreasing CaO concentration. An increase in the molar volume of slag was also observed with increasing temperature.